Assessment of carotid intima-media thickness in patients with type 2 diabetes mellitus and arterial hypertension - Irina Arkad'evna Bondar'; Alexander Aristarkhovich Demin; Olesya Yur'evna Shabel'nikova; Viktoriya Alexandrovna Onyanova (Сахарный диабет)
Aim.  Atherosclerosis is one of the most important complications of type 2 diabetes mellitus (T2DM). In the present study, we aimed to assess the carotid intima-media thickness in type 2 diabetes patients with the arterial hypertension (AH) comorbidity. Materials and Methods.  96 patients with T2DM and AH (30M/66F, aged 53.4?5.4 years, duration of diabetes 7.7?7.5 years) and 30 hypertensive patients without diabetes (12M/18F, aged 53.1?6.0 years) were enrolled in this study. Stiffness indices for right and left common carotid arteries were assessed with noninvasive ultrasound method in both groups. Results. Difference in the intima-media thickness was statistically significant between diabetic and euglycemic patients (1.26?0.17 mm vs. 1.10?0.14 mm, respectively; p0.05), in contrast with their counterparts with longer experience of T2DM (1.27?0.17 mm vs. 1.10?0.14 mm; p